A knowledge management framework for studying the child obesity - Suteeca R. (2017)
© 2016 IEEE. The problem of obesity in children is an important problem because it could lead other disease. The major challenge in the current childhood obesity prevention is the diversity of information. Not all of the information is a valid medical knowledge, such as some local belief. Therefore, applying the invalid information to children often cause more harm than good. In this work, we present a knowledge management framework to collect and analyze the related knowledge about the children obesity prevention. The process of this framework is based on the knowledge creation theory.